1996
DOI: 10.3109/02656739609023527
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-growth inhibition by induced hyperglycaemia/hyperlactacidaemia and localized hyperthermia

Abstract: The present study was undertaken to exploit pathophysiological properties of solid tumours for a tumour-specific therapy. Experiments were carried out on DS-sarcomas implanted s.c. in the hind foot dorsum of Sprague Dawley rats. Treatment strategies included tumour acidification, lactate accumulation and disturbance of the microcirculation by induced systemic hyperglycaemia/hyperlact-acidaemia (15-25/10 mmol/L; for 60 min) as well as localized hyperthermia (water-bath; 43 degrees C, 30 min.). A special infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…A lthough these animals died earlier than expected too, most of their tumours showed an extensive necrosis af ter hyper-thermic perfusion with hyperlactaci daemia. A volume shrinkage of the DS-sarcomas could be proved, supporting the results of a previous study (Mueller-Klieser et al 1996).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A lthough these animals died earlier than expected too, most of their tumours showed an extensive necrosis af ter hyper-thermic perfusion with hyperlactaci daemia. A volume shrinkage of the DS-sarcomas could be proved, supporting the results of a previous study (Mueller-Klieser et al 1996).…”
Section: Discussionsupporting
confidence: 90%
“…A fter the musculature had reached the demanded temperature of 38 and 40 ë C, respectively, perfusion was continued for a further 60 min in all groups. In groups III, IV and V the desired level of hyperlactacid aemia was achieved by adding adequate amounts of the previously described inf usion solution of lactic acid, glucose and Tris bu er to the perfusate (Mueller-Klieser et al 1996). A fter removal of the cannulas at the end of the perfusion, the femoral vessels were repaired with 10/0 non-absorbab le single sutures, while the wound was closesd applying absorbable running sutures.…”
Section: Aterials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…meta-Iodobenzylguanidine is one of the inhibitors of mitochondrial complex 1, acting as proton extrusion inhibitors (or hyperglycemia) and then decreasing pH i in cancer cells. 100,[109][110][111] However, this drug is normally used as a radioiodine therapy agent, and the dose used for radioiodine therapy is not high enough to perform a strong inhibition on proton transportation. Dinitrophenol (DNP), a new type of chemotherapeutic drugs, has also shown a remarkable enhancement in glycolysis with the increase of blood pressure at a low dose.…”
Section: Alternative Methods To Manipulate the Ph E /Ph I Ratiomentioning
confidence: 99%
“…According to the procedure of sCMT we induced high levels of hyperglycaemias to augment lactatacidosis in blood and tumour tissue [8]. Preclinical studies have shown that an acidic environment enhances heat-induced apoptosis [24] and that hyperglycaemia induced lactatacidosis combined with hyperthermia resulted in extensive tumour-growth inhibition [25].…”
Section: Discussionmentioning
confidence: 99%